Physical visualization of math concepts using LEGO Mindstorms - Andrés-David; Wilson Javier Pérez-Holguín (OmniaScience, 2020)
Educational robotics has become one of the most effective methods to teach STEM concepts in a practical and didactic way at all educational level. In this context, the LEGO Mindstorms robotic platforms have been widely used due to their versatility ease of use and modularity. Despite this, most of the papers focus on K-12 and undergraduate levels, with little information reported in the literature about educational experiences at the graduate level. This article deals with the use of educational robotics for the teaching of mathematical concepts at the graduate level, and more specifically on the physical visualization of metrics (Euclidean, Taxicab, and Infinity), and the convergence of Cauchy's succession using a mobile robots LEGO Mindstorms NXT. The educational experience was applied to a group of graduate students who offered good comments on this type of educational activity and its usefulness to understand the mathematical concepts addressed. It was observed that this type of educational experiences motivates students to use mathematical concepts in interdisciplinary problems and encourages them to understand their functionality and application in the real world.